RESPONS MADRASAH TERHADAP GLOBALISASI - Thoyib, Muhammad (Jurnal Pendidikan Islam, 2016)
This paper intends to explore the spirit of globalization in the madrassa. The analysis is done through the study of conceptual curriculum which is assumed to contain some elements of globalization such as democracy, autonomy, international markets, superiority and competitiveness. The development of quality of madrassa with global orientation develop four main competencies: 1) academic, 2) personal, 3) social and 4) spiritual competencies. They cover six elements, namely: (1) knowledge and cognition, (2) understanding and affection, (3) the ability to execute a task or job well, (4) value, that covers good behavior behavior that manifest themselves in a pupil, (5) the attitude , is a fast reaction to external stimuli, and (6) high interest in the positive range. To implement curriculum based on globalization management, madrasas can apply strategies such as: 1) self-management curriculum, creative and innovative spirit of autonomy and globalization; 2) master of science, personal formation, and mastery of social problem-solving skills; 3) master developmentally specific competency based learners.